Recovery of glucose and acetic acid from Piper betle Linn leaves by subcritical water hydrolysis - Rahmah, Nur Lailatul; Mustapa Kamal, Siti Mazlina; Sulaiman, Alifdalino; Taip, Farah Saleena; Siajam, Shamsul Izhar (Gadjah Mada University, 2025)
Piper betle Linn (PBL) leaves contain high carbohydrates, which can be hydrolyzed into glucose and acetic acid by hydrolysis. Subcritical water hydrolysis (SWH) is an environmentally friendly method that uses water as a solvent and is suitable for hydrolysis. Thus, this study aims to evaluate the glucose and acetic acid recovered from PBL leaves using SWH. Using a factorial design, SWH was performed under different process conditions (temperature range 100 to 275°C and time range 5 to 30 min). Glucose and acetic acid were determined using high-performance liquid chromatography (HPLC) with a refractive index (RI) detector. The ANOVA results show that temperature, time, and the interaction of temperature and time significantly impact glucose yield and acetic acid concentration. The particle size of PBL leaves of 220.70± 2.33 µm was effective, and it can be used to recover glucose and acetic acid by SWH. The yield of glucose and acetic acid shows a different trend, with glucose degrading to acetic acid. The highest glucose concentration was achieved at 200°C for 5 min (6.143 mg/g extract), while the highest acetic acid concentration was obtained at 225°C for 20 min (2.856 mg/g extract).